Concept and Implementation of The Independent Learning Curriculum at Elementary School in Bengkulu City - Putra Jaya, Untung; Danim, Sudarwan; Badeni, Badeni; Putra, Syalendra (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this research is to provide a comprehensive analysis of the idea of an autonomous learning curriculum at Elementary Schools in Bengkulu City, including everything from planning and implementation to challenges and solutions. This study employs a qualitative methodology. Through observation, documentation, and interviews, data was gathered. Interactive data analysis techniques, as developed by Miles Huberman, were used to analyze the data. The concept of developing and implementing the independent learning curriculum at Elementary Schools in Bengkulu City was found to have been accomplished through two processes: educating all school stakeholders about the four curriculum pillars and setting up the necessary infrastructure, like the e-learning system and Independent Learning Platform, to support the curriculum's implementation. The planning of socialization events, workshops, and technical guidance for the implementation of the independent learning curriculum must continue if Elementary Schools in Bengkulu City are to successfully adopt the independent curriculum.